2014
DOI: 10.1590/0004-282x20140145
|View full text |Cite
|
Sign up to set email alerts
|

Is there correlation between cognition and functionality in severe dementia? The value of a performance-based ecological assessment for Alzheimer’s disease

Abstract: Objective: Besides significant cognitive decline, patients in later stages of Alzheimer's disease (AD) also present global functional impairment, usually reported by their caregivers. This study searched for preserved activities of daily living by investigating correlations among specific instruments for severe dementia with a performance-based functional scale. Method: A sample of 95 moderate to severe AD patients and their caregivers underwent a neuropsychological battery consisting of screening tools, the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
1
9
0
5
Order By: Relevance
“…The moderate stage shows almost a comparable decline in both IADL and BADL, differing from the mild stage when deficits in only IADL are prevalent [21]. A study using the total scores from a neuropsychological battery and performance-based measure of ADL found a significant relationship between the two scores in a sample of persons with moderate or severe AD [22]; however, the specifics of cognitive and functional impairment in the later stages are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The moderate stage shows almost a comparable decline in both IADL and BADL, differing from the mild stage when deficits in only IADL are prevalent [21]. A study using the total scores from a neuropsychological battery and performance-based measure of ADL found a significant relationship between the two scores in a sample of persons with moderate or severe AD [22]; however, the specifics of cognitive and functional impairment in the later stages are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence to suggest that three factors – cognition, physical performance, and behavioral and psychological symptoms of dementia (BPSD) – directly affect ADL and mediates the effects of other factors, such as aerobic fitness on ADL (Figure ). Studies have demonstrated a positive association between global cognition and ADL well into the severe stage of AD (Allain et al, ; Delva et al, ; Wajman, Oliveira, Marin, Schultz, & Bertolucci, ), and the association is stronger as AD progresses over time (Liu‐Seifert et al, ). Quantitatively, a one point worsening in global cognition, as measured by the Mini‐Mental State Examination (MMSE), is associated with a three point decline in ADL, as measured by the Disability for AD (DAD) scale (Arrighi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Processos funcionais dependem dos contextos em que ocorrem, portanto quanto mais próxima a avaliação funcional estiver do contexto em que ela é realizada rotineiramente, mais fidedigna a avaliação do desempenho (Giles, 2014). É possível observar pouca disponibilidade de instrumentos de avaliação funcional detalhada, integrando diferentes pontos de vista e que permitam inferir conjuntamente a cognição, de forma que nos idosos com demência a funcionalidade seja abordada como um importante parâmetro de estado de saúde (Wajman et al, 2014).…”
Section: Executive Functioning Performance Test (Efpt)(baumunclassified